Respuesta :
Given:
mass of satellite, m = 1710 kg
altitude, h = [tex]2.6\times 10^{6} m[/tex]
G = [tex]6.67\times 10^{-11} [/tex]
we know
mass of earth, [tex]M_{E}[/tex] = [tex]5.972\times 10^{24} kg[/tex]
Here, according to question we will consider
[tex]2M_{E}[/tex] = [tex]11.944\times 10^{24} kg[/tex]
radius of earth, [tex]R_{E}[/tex] = [tex]6.371\times 10^{6} m[/tex]
Formulae Used and replacing [tex]M_{E}[/tex] by [tex]2M_{E}[/tex] :
1). [tex]v = \sqrt{\frac{2GM_{E}}{R_{E} + h}}[/tex]
2). [tex]T = \sqrt{\frac{4\pi ^{2}(R_{E} + h)^{3}}{2GM_{E}}}[/tex]
3). [tex]KE = \frac{1}{2}mv^{2}[/tex]
4). [tex]Total Energy, E = -\frac{2GM_E\times m}{2(R_{E} + h)}[/tex]
where,
v = orbital velocity of satellite
T = time period
KE = kinetic energy
Solution:
Now, Using Formula (1), for orbital velocity:
[tex]v = \sqrt{\frac{6.67 \times 10^{-11} \times 11.944 \times 10^{24}}{6.371 \times 10^{6} + 2.6 \times 10^{6}}[/tex]
v = [tex]9.423 \times 10^{3}[/tex] m/s
Using Formula (2) for time period:
[tex]T = \sqrt{\frac{4\pi ^{2}(6.371\times 10^{6} + 2\times 10^{6})^{3}}{6.67\times 10^{-11}\times 9.44\times 10^{24}}}[/tex]
[tex]T = 6.728\times 10^{3} s[/tex]
Now, Using Formula(3) for kinetic energy:
[tex]KE = \frac{1}{2}(9.44\times 10^{24})(9.42\times 10^{3})^{2}[/tex]
[tex]KE = \frac{1}{2}(1710)(9.42\times 10^{3})^{2} = 7.586\times 10^{10} J[/tex]
Now, Using Formula(4) for Total energy:
[tex]E = -\frac{6.67\times 10^{-11}\times 9.44\times 10^{24}\times 1710}{2( 6.371\times 10^{6} + 2.6\times 10^{6})}[/tex]
[tex]E = - 7.59\times 10^{10} J[/tex]